Health and rights: tensions of a disputing SUS, molecularities - Merhy, Emerson (Saúde e Sociedade, 2012)
According to the point of view that "every life is worth it", this text, based on a conference made by the author at the XII Congress of Public Health of São Paulo, discusses certain areas of tension that are operative in the field of health regarding the relationship between health and rights. In spite of recognizing the molar constitutive elements of this field, it defends the idea that the vital fights inside the current model, in which there are lives that are more worth it than others, must happen inside the molecularity of the work in health, inside the management and inside the care. It has to put the locus of practice as a key to the effective production of new modes of producing lives, where the differences are wealth and the vicinity between distinct forms of knowledge is nuclear to the making of bets. In these bets the richness of existential connections is the best way of betting that life production expresses the most fundamental aspect when building the field of health. Taking support from authors that discuss micro politics and schizoanalysis, the author tries and conducts a reflection about the implications of this "constructive regard".